Health Services Utilization and Associated Factors among Internally Displaced Persons in South Wollo Zone, North-Eastern Ethiopia - Abdulhamid , Y.; Toyeb, Y.; Yitbarek, W. (International Journal of Health Sciences, 2024)
Purpose: To assess the health services utilization and associated factors among internally displaced persons at South Wollo zone, North-Eastern Ethiopia, 2023. Methodology: A cross-sectional study was conducted among IDPs in South Wollo Zone, North Eastern Ethiopia. The study was conducted from July 15 to August 15/2023. A structured questionnaire was administered to a random sample of 422 IDPs, collecting data on demographics, health status, health service utilization, and barriers to accessing healthcare. The data were entered into Epi-Data version 3.2, then, exported to SPSS version 25 for analysis. Logistic regression analyses were performed to identify factors associated with health service utilization. The Hosmer and Lemeshow test was used to determine the model's goodness of fit. Findings: The study found that 61.1% (95% CI: 58.1- 67.2) of IDPs reported using health services within the past three months. Key factors influencing health service utilization among internally displaced persons were occupation (being a house wife [AOR:5.16, 95% CI: 2.42-11.00], daily laborers [AOR:3.27, 95% CI: 1.63-6.62], merchant [AOR;3.61;95%CI ;1.33-9.77] ,family size [AOR:2.72, 95% CI: 1.70-4.35], having an average monthly income of 1001-2000 birr [AOR:1.82, 95% CI:1.13-2.95], and duration of encampment [AOR: 1.77, 95% CI: 1.13-2.77] which are found to be statistically associated factors. Unique contribution to theory, policy and practice: Health service utilization among IDPs in south Wollo zone is influenced by a complex interplay of duration of encampment, monthly income; occupational status and family size factors. Addressing these barriers through targeted interventions, improved income, and comprehensive information dissemination is essential to enhance healthcare utilization for this vulnerable population. Future research should focus on longitudinal studies to better understand the evolving needs of IDPs and the long-term effectiveness of implemented strategies.